An Investigation of Perceived Risk at the Brand Level - Peter, J. Paul; Ryan, Michael J. (Journal of Marketing Research, 1976)
Perceived risk is conceptualized in terms of expected negative utility associated with automobile brand preferences. Empirical evidence supports the notion that importance of loss is more useful as a segmentation variable than as a component in a multiplicative model. The findings also Indicate that probability of loss may operate at the handled risk level and importance of loss at the inherent risk level.